Block Her Entry, Keep Her Down and Push Her Out: Gender discrimination and women journalists in the Arab world. (2nd January 2016) - Melki, Jad P.; Mallat, Sarah E.
Abstract : This study examines why female journalists in an Arab country continue to be marginalized. It hypothesized that a set of interrelated factors, pertaining to gender discrimination, sexual harassment, and the lack of a legally and socially enabling environment, work together to systematically discourage and block women's entry into the news field, push those who made it out of the profession, and keep those who have endured down and siloed in specific roles away from decision-making and policy-setting positions. The study uses a mixed-methods approach, including a survey of 250 Lebanese, Arab and international female journalists working in Lebanon, qualitative interviews with 26 female journalists, as well as analysis of ownership documents and minutes of board meetings. Findings suggest that structural, institutional and cultural obstacles that have faced women for centuries around the globe continue to operate with potent effects in Lebanon, and by extension in the Arab region.